A new freshwater crab species of the genus Vela Bahir & Yeo, 2007 (Decapoda: Brachyura: Gecarcinucidae) from the Western Ghats of Karnataka, India - Pati, Sameer Kumar; Bajantri, Parashuram Prabhu; Hegde, Gopalkrishna Dattatraya (Zootaxa, 2023)
Vela bandhavya sp. nov., a new species of gecarcinucid crab is described from the Central Western Ghats, Uttara Kannada district, Karnataka state, India. The new species can be immediately distinguished from three other species of Vela Bahir & Yeo, 2007, mainly by its short male sternopleonal cavity and a relatively shorter distal article of the male first gonopod. The diagnosis of Vela is revised to accommodate the new species, and an illustrated identification key is provided for all four species. An anomalous adult male crab, with a pair of pleopods on the pleonal somite 5 in addition to the male gonopods, is also reported.